1991
DOI: 10.1007/bf02273884
|View full text |Cite
|
Sign up to set email alerts
|

A special tissue expander in combination with extensive scalp-lifting

Abstract: Although posterior closure of male pattern baldness is usually accomplished in two procedures when using extensive scalp-lifting, there is the occasional patient who will require three operations because of very poor scalp laxity. A newly developed horseshoe-shaped tissue expander was designed for these patients so that a third procedure could be eliminated. This differential expander is actually placed during the first extensive scalp-lifting operation. This differs from the conventional placement as a separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…These results suggest that the factor driving pedicle skin expansion may be the mechanical stretch resulting from the rapid expansion of the underlying antlerogenic tissue. It has been shown that new skin is produced, in experimental condition, after stretching by subcutaneous insertion of an inflation‐controlled tissue expander (Austad et al, 1982; Brandy, 1991; Timmenga et al, 1989). Austad et al (1982) concluded that skin expansion is a physiological process to accommodate an enlarging mass beneath it by increasing surface area.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the factor driving pedicle skin expansion may be the mechanical stretch resulting from the rapid expansion of the underlying antlerogenic tissue. It has been shown that new skin is produced, in experimental condition, after stretching by subcutaneous insertion of an inflation‐controlled tissue expander (Austad et al, 1982; Brandy, 1991; Timmenga et al, 1989). Austad et al (1982) concluded that skin expansion is a physiological process to accommodate an enlarging mass beneath it by increasing surface area.…”
Section: Discussionmentioning
confidence: 99%
“…As described in other articles, 20,21 most extensively bald patients can be closed posteriorly with two extensive scalp‐lifting operations; namely, a bilateral occipitoparietal scalp‐lift and a bitemporal scalp‐lift 3 months later. Because the author 22 has proved statistically that approximately 60% of the stretching in extensive scalp‐lifting comes from the area inferior to the nuchal ridge (owing to lack of restrictive galea in that region), it can be calculated from that figure that approximately three extra operations would be needed to acquire closure.…”
Section: Design Conceptsmentioning
confidence: 99%
“…Primary closure is possible after surgical excision of small or localized lesions, while larger lesions require more complicated reconstructive methods, such as tissue expansion applications, prior to excision. [5][6][7] In order to replace the hair-bearing scalp defect, the use of local tissue of similar quality and structure is optimal. For reconstruction of large lesions or defects, tissue expansion presents a useful option.…”
Section: Introductionmentioning
confidence: 99%